A role for kinesin heavy chain in controlling vesicle transport into dendrites in Drosophila - Henthorn, Kristina Schimmelpfeng (The American Society for Cell Biology, 2011)
The unique architecture of neurons requires the establishment and maintenance of polarity, which relies in part on microtubule-based transport to deliver essential cargo into dendrites. To test different models of differential motor protein regulation and to understand how different compartments in neurons are supplied with necessary functional proteins, we studied mechanisms of dendritic transport, using Drosophila as a model system. Our data suggest that dendritic targeting systems in Drosophila and mammals are evolutionarily conserved, since mammalian cargoes are moved into appropriate domains in Drosophila. In a genetic screen for mutants that mislocalize the dendritic marker human transferrin receptor (hTfR), we found that kinesin heavy chain (KHC) may function as a dendritic motor. Our analysis of dendritic and axonal phenotypes of KHC loss-of-function clones revealed a role for KHC in maintaining polarity of neurons, as well as ensuring proper axonal outgrowth. In addition we identified adenomatous polyposis coli 1 (APC1) as an interaction partner of KHC in controlling directed transport and modulating kinesin function in neurons.